Positive management of universities: A model of motivation to strive for scientific excellence - Beata A. Basińska; Krzysztof Leja; Magdalena Szufllita-Żurawska (Entrepreneurial Business and Economics Review (EBER), 2019)
Objective: The aim of the article is to conceptualise a model of work motivation in the management of universities striving for scientific excellence. Research Design & Methods: The most relevant for our aim is the self-determination theory that is applied to the work and organisational domain. We used a narrative literature review. Findings: The proposed model is derived from the self-determination theory. It includes three types of motivation: autonomous motivation, controlled motivation, and amotivation, as well as three psychological needs, i.e. autonomy, mastery, and purpose. These motives and needs can interact to enhance scientific effectiveness further. Implications & Recommendations: Universities need innovative staff who can contribute to strengthening scientific productivity and enhance the influence of the university at the international level. Contribution & Value Added: Connection of three perspectives - institutional, individual and scientific disciplines - will capture the complexities of managing work motivation oriented to scientific effectiveness.
Keywords: I23; 330; motivation; university management; scientific effectiveness; psychological needs; positive organisational scholarship; self-determination theory